Literacy and Health Wearables - Madeira, Filipe (2022)
The increasing use of smart health devices is causing relevant behavioral changes, introducing new forms of health promotion. However, most of these interventions are the result of a self-personal, derived from each one's knowledge of their state of health and considering the goals that each one establishes for themselves. These devices usually have software applications designed to collect and display data, with the aim of reaching many users, irrespective of their literacy, health condition and socio-demographic characteristics.